Progressive Literacy Task: Design Strategy of digital literacy and competencies in learning outcomes - Ahmad Zuhudy Bahtiar; Ahdar; Nur Eva Yanti (Al-Ishlah: Jurnal Pendidikan Islam, 2023)
Raising interest in reading and digital literacy skills is currently a big challenge for teachers amid the many information vortices at this time. Attention and awareness of reading are still very low among students. This study aims to make the right learning strategy to form a culture of literacy among college students. This research is descriptive research to find the right model for teaching students about digital literacy both conceptually and in skills. The data in this study is to reveal (1) student learning motivation, (2) the use of learning strategies, (3) digital literacy skills, (4) and the formation of a literacy culture. Data collection techniques in descriptive research are through direct observation, questionnaires, independent assignments, and performance. based on a collection of various data used to formulate appropriate learning strategy designs for students completing instructional technology courses .